Role of the medial prefrontal cortex and nucleus accumbens in an operant model of checking behaviour and uncertainty. (27th September 2017) - d'Angelo, Camilla; Eagle, Dawn M.; Coman, Cristina-M.; Robbins, Trevor W.
Background: Excessive checking is a common, debilitating symptom of obsessive–compulsive disorder. To further examine cognitive processes underpinning checking behaviour, and clarify how and why checking develops, we designed a novel operant paradigm for rats, the observing response task. The present study used the observing response task to investigate checking behaviour following excitotoxic lesions of the medial prefrontal cortex, nucleus accumbens core and dorsal striatum, brain regions considered to be of relevance to obsessive–compulsive disorder. Methods: In the observing response task, rats pressed an 'observing' lever for information (provided by light onset) about the location of an 'active' lever that provided food reinforcement. Following training, rats received excitotoxic lesions of the regions described above and performance was evaluated post-operatively before histological processing. Results: Medial prefrontal cortex lesions selectively increased functional checking with a less-prominent effect on non-functional checking and reduced discrimination accuracy during light information periods. Rats with nucleus accumbens core lesions made significantly more checking responses than sham-lesioned rats, including both functional and non-functional checking. Dorsal striatum lesions had no direct effect on checking per se, but reduced both active and inactive lever presses, and therefore changed the relative balance between checking responses and instrumental responses. Conclusions: These results suggest that the medial prefrontal cortex and nucleus accumbens core are important in the control of checking, perhaps via their role in processing uncertainty of reinforcement, and that dysfunction of these regions may therefore promote excessive checking behaviour, possibly relevant to obsessive-compulsive disorder.